IMPLEMENTASI PERJANJIAN PEMBIAYAAN JUAL BELI (MURABAHAH) DI BANK NEGARA INDONESIA ( BNI ) SYARIAH CABANG SEMARANG - Moch Faizul Khakim; Gunarto Gunarto (Jurnal Akta, 2017)
One form of financing agreement provided by Bank BNI Sharia is murabahah, which is a form of trust and sale of certain goods, between banks and customers. The bank buys the required item and sells it to the respective customer at the cost of the acquisition plus the agreed benefit. The purpose of this study entitled Implementation of Sale and Purchase Agreement (murabahah) in Bank BNI Sharia Branch Semarang is to find out how the procedures and requirements in the implementation of Buy and sell Financing Agreement (murabaha) at Bank BNI Sharia Branch Semarang and problems often faced in Murabahah Financing Agreement as well as efforts to overcome the problem of Implementation of Murabahah Financing Agreement at Bank BNI Sharia Branch of Semarang. This research is a descriptive analysis using sociological juridical research methods and field research, based on the results of research concluded that the stages or procedures and requirements in Murabahah Financing Agreement at Bank BNI Sharia Branch Semarang is Application, Investigation, Financing Analysis, Letter of Agreement on Financing Agreement, Signing of Murabahah Agreement, Withdrawal, Installment Calculation, Installment Payment and Repayment. In the implementation of the Murabahah Financing Agreement, Bank BNI Sharia often faces several problems, especially in terms of murabahah financing for houses / property, based on observations the authors conclude there are some weaknesses or difficulties that become problem in murabahah financing, that is in terms of Human Resources (HR) and the provisions of the National Sharia Council Fatwa. BNI Sharia Bank's efforts to solve a problem when one party does not fulfill its obligations, BNI Sharia Bank applies its settlement clause by way of deliberation and kinship, if in the above manner can not reach agreement, then the final effort is settled through local District Court. It is suggested to Bank BNI Sharia to distribute murabahah financing always pay attention to applicable law. If the murabahah financing is not able to comply with the applicable law, then this murabahah product should not be marketed temporarily pending the issuance of new regulations that support the implementation of this murabahah product. Keywords: Murabahah Agreement, PT. Bank BNI Sharia Branch Semarang